2000
DOI: 10.1007/bf02236559
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative intra-abdominal free gas after open colorectal resection

Abstract: By the sixth postoperative day 80 percent of patients had no subdiaphragmatic free gas on an erect chest radiograph regardless of the presence of a drainage tube. The erect chest radiograph may therefore be a simple and readily available adjunct in the evaluation of postoperative abdominal pain, especially after the sixth postoperative day when a similar prior examination is done routinely on the fourth postoperative day for comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…This is similar to that reported by Nielsen et al [7]. Other authors reporting the incidence of postoperative pneumoperitoneum noted rates of 21%-53% within the first 3 postoperative days [1,2,5,8,9]. In most of these reports, pneumoperitoneum had resolved by 5-18 days postoperatively.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This is similar to that reported by Nielsen et al [7]. Other authors reporting the incidence of postoperative pneumoperitoneum noted rates of 21%-53% within the first 3 postoperative days [1,2,5,8,9]. In most of these reports, pneumoperitoneum had resolved by 5-18 days postoperatively.…”
Section: Discussionsupporting
confidence: 79%
“…In most of these reports, pneumoperitoneum had resolved by 5-18 days postoperatively. The factors that facilitate the absorption of air are a high body-mass index and female gender [5,[7][8][9] whereas age, type or duration of operation, and the presence of drains has no influence [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no consensus as to what should be considered as a normal or acceptable duration of retained postoperative intraperitoneal gas, but most authors reported short durations of several days at the most, with the majority describing nearly complete disappearance of the retained gas within approximately 1 week. [1][2][3][4][5][6] Nevertheless, in cases where the finding of postoperative free intraperitoneal air is accompanied by clinical signs and symptoms such as abdominal pain, fever, leukocytosis, or peritoneal signs, prompt diagnostic and therapeutic measures should be undertaken without delay.…”
Section: Discussionmentioning
confidence: 97%
“…They found that free air was significantly more often present in men and asthenic patients, but they could not demonstrate an effect of age and the type of the procedure on the duration of postoperative PP. Tang et al [9]studied 75 consecutive patients for postoperative free air, and 89% of the patients had no free air by the postoperative first week, while only 6% had retained air by postoperative day 10. They could not show any significant effect of duration of surgery, BMI, postoperative ileus and drainage catheters on the disappearance of free air postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In most instances postoperative PP resolves within a week, but there are reported cases of PP lasting as long as 10–24 days [5, 6, 7, 8, 9, 10]. In order to prevent negative laparotomies it is important to differentiate the post-operative delayed PP from ‘surgical PP’.…”
Section: Introductionmentioning
confidence: 99%